Estudo populacional de Anopheles darlingi utilizando análise de RAPD e seqüenciamento de genes mitocondriais - Angêlla, Aline Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
O fungo termo dimórfico, Paracoccidioides brasiliensis é o agente etiológico da Paracoccidioidomicose (PCM), a micose sistêmica mais prevalente da América Latina. Este fungo vem sendo frequentemente isolado de amostras clínicas, tecidos de tatu (Dasypus novemcinctus) e recentemente foi também isolado de cão. Este trabalho avaliou a transição de micélio para levedura (M-L), a termo tolerância e o perfil de virulência em nove isolados de P. brasiliensis (quatro de pacientes humanos, quatro de tatus e um de cão), bem como a sua relação com a seqüência parcial e expressão do gene hsp70 (Heat Shock Protein 70) através de Real Time RT-PCR. Tanto os dados morfológicos como moleculares se mostraram variáveis dentre os diferentes isolados. Alguns destes dados, como sequenciamento e morfologia leveduriforme corroboram com a divisão de nossos isolados nas duas espécies crípticas simpátricas previamente propostas por Matute et al (2006). Nossos resultados confirmam que a HSP70 pode ser um importante fator de virulência por estar associado à termo tolerância, mas sua expressão parece não ser diretamente associada a altos padrões de virulência.

The thermo dimorphic fungus Paracoccidioides brasiliensis is the etiological agent of Paracoccidioidomycosis (PCM), the most prevalent systemic mycosis in Latin America. The previous phylogenetic species recognition proved the existence of, at least, three cryptic species in this pathogen. In this work we evaluated the mycelia to yeast (M-Y) transition, thermo tolerance and virulence profiles of nine isolates of P. brasiliensis, (including members of two of the three species) as well as its relation to the partial sequence and expression of hsp70 gene. It was observed a large phenotypic variability concerning the M-Y transition. The isolates Bt84 and T10 took more time to convert to the yeast form. These same isolates presented stretched yeast cells at 36°C, instead of the typical round cells. It was also observed arthroconidia production during the M-Y transition for some of the nine isolates studied. The hsp70 expression showed to be variable among our isolates. The partial sequencing of hsp70 gene resulted in a Neighbour Joining tree that divided our isolates in two main groups. Conclusions: Our data confirm that hsp70 gene might be an important virulence factor, associated with the thermo tolerance, but its expression does not seem to be directly related to high virulence profiles. We also presented some preliminary results about mycological characters that could be important candidates for morphologic markers for species recognition, as well as the partial sequencing of one member of the hsp70 gene family that allowed the separation of our isolates in two clusters, that correspond to the two sympatric cryptic species that occur in our PCM hyper endemic area (Botucatu, SP, Brazil).
Keywords: Mosquitos - Genética; Genetica de populações; Paracoccidioides brasiliensis; Micose sistêmica; Systemic mycosis